Literature Review of the Concepts of Elasticity and Oscillation in Fundamental Physics 1: Various Research Variables, Educational Level, and Instructional Methods - Yudi Kurniawan; Andi Suhandi; Achmad Samsudin (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study is to provide a comprehensive overview of the concepts of elasticity and vibration, based on research variables, educational levels, and teaching strategies. The article is organized based on queries conducted in reputable international databases, such as Scopus and Web of Science, using content analysis techniques, such as analyzing article identities, educational information, synthesis of used approaches, and measured variables. In the topics of elasticity and oscillation, qualitative, quantitative, and hybrid methods can be used to investigate a variety of variables, as indicated by the research findings. Among these variables are conceptual comprehension, academic achievement, and student interest. In addition, the educational level being investigated determines how elasticity and oscillation concepts are taught in the classroom. These findings highlight the significance of utilizing a variety of instructional strategies to effectively convey the concept of elasticity and oscillation to measure various variables with practical consideration on educational settings. In addition, our review provides a comprehensive list of common variables research that can serve as a valuable resource for educators and researchers seeking to enhance their elasticity and oscillation research. This systematic review highlights the need for additional research on effective teaching methods for oscillation and provides educators and researchers with useful insights.